Comparison of Plaque Index (PI) calculation time between a Digital Dental Calculator (DDC) app and the manual method: a quasi-experimental study - Putri, Syaida Erma; Yandi, Satria; Amran, Ricky; Anggraini, Netta; Ningrum, Valendriyani; Lee, Shih- Chieh (Universitas Padjadjaran, 2025)
Introduction: Dental plaque is a soft biofilm that accumulates on the tooth surface and around the gingival margin. If not properly managed, it can lead to oral diseases such as gingivitis. The manual assessment of the Plaque Index (PI) has several limitations, including variability in the number of teeth examined, assessor subjectivity, and potential inaccuracy, particularly at low or high plaque levels. To overcome these challenges, a technology-based approach is needed to enhance standardization and consistency. This study aims to compare the calculation time of PI using a Digital Dental Calculator (DDC) app and the conventional manual method. Methods: A quasi-experimental study with a one-group posttest-only design was conducted among 70 dental students at Universitas Baiturrahmah who had completed the periodontics module and met inclusion and exclusion criteria. Participants performed PI calculations using both manual and digital methods under standardized conditions. The time required for each method was measured in seconds. Data were analyzed using descriptive statistics (mean ± SD) and the Mann–Whitney U test to compare calculation times between the two methods, with a significance level of p < 0.05. All analyses were conducted using IBM SPSS Statistics version 26.0 to ensure transparency and reproducibility. Results: The mean PI calculation time using the manual method was 178.74 seconds, while the digital DDC method required 143.97 seconds, showing a mean difference of 34.77 seconds. Statistical analysis revealed a highly significant difference between the two methods (p < 0.001), indicating that the DDC significantly reduced PI calculation time. Conclusion: The use of the Digital Dental Calculator (DDC) significantly shortened the time required to calculate the Plaque Index compared to the manual method. These findings highlight the potential of digital tools to improve efficiency, standardization, and accuracy in both clinical and educational dental settings.